SMAR1 promotes immune escape of Tri-negative Breast Cancer through a mechanism involving T-bet/PD-1 Axis - Xiaohua, Wang; Hongxia, Xu; Rong, Deng; Pingping, Wu; Xing, Huang; Yichao, Zhu; Cheng, Chen (Cellular and Molecular Biology, 2018)
This study was aimed at investigating the specific molecular mechanisms involved in the regulation of immune escape of triple-negative breast cancer (TNBC) by SMRI, so as to provide a new clinical treatment target for the disease. Mouse original 4T1 breast cancer cells were inoculated subcutaneously in BALB/C to establish TNBC mouse model. CD8+T cells with immunological effects were selected from mouse thymus glands for primary culture. The CD8+positive T cells were infected with lentivirus interference vectors, and the proliferation of CD8+ T cells were determined by trypan blue staining and flow cytometry. CD8+T cells and 4T1 cells were cultured together so as to determine the cytotoxic effects of SMAR1-downregulated CD8+ T cells on tumor cells and the expression of cytokines (IFN-Î³, TNF-Î±, IL-2, IL-4 and IL-6). The expressions of SMAR1, T-bet and PD-1 were assayed by Western blot. SMAR1-downregulated CD8+T cells were injected into 4T1 tumor-bearing mice through the caudal vein, and the growth of tumor in mice was monitored. Following the infection of CD8+T cells with SMAR1-downregulated lentiviral system, cell apoptosis level was decreased significantly (control vs. sh-SMAR1: 32.23 ± 12.4 % vs. 18.28 ± 8.93 %, p < 0.05). Results from trypan blue staining experiments showed that the proliferation of CD8+ T cells in the SMAR1-downregulated group was significantly increased; SMAR1-downregulated CD8+ T cells promoted the production of IFN-Î³, TNF-Î±, IL-2, IL-4 and IL-6 in 4T1 breast cancer cells (p < 0.05). Western blot showed that SMAR1 down-regulation led to significant upregulation of T-bet, while PD-1 was downregulated, when compared to the control group (p < 0.05). The downregulation of SMAR1 was associated with significant reduction in tumor size in mice (p < 0.05). SMAR1 downregulation enhances the tumor killing effect of CD8+T cells by activating T-bet and down-regulating PD-1